KONTESTASI NEGARA DI TENGAH PANDEMI COVID-19 - SUSHANTI, SUKMA (Jurnal Ilmiah Widya Sosiopolitika; Vol 2 No 1 (2020): ISU PARIWISATA DAN KESEHATAN DALAM PERSPEKTIF SOSIAL DAN POLITIKDO - 10.24843/JIWSP.2020.v02.i01.p02, 2020)
International disease become the transnational issue that has enriched the studies in International Relations. It refers to the recent situation of COVID-19 pandemic, which is currently become the global concern. Then, politics and health interlinked each other. The main objective of the research to describe and explain about health issue is inevitable in demonstrating state interest. Desk research based on the valid sources helped build justification that health and international politics become integral part of the relation beween the actors. The scope of state foreign policy already adopt the health issues as the one of important agenda, in which created the competition in the international field. This condition supported by the shifting of the global order in the international politic constellation as the implication of COVID-19 pandemic. Keyword : international disease, international relation, COVID-19 pandemic, health issues. Foreign policy